A estrutura do habitat controla a distribuição e diversidade da Odonatofauna?. - Souza, Aline Mariano de (2013)
The fact that the complexity and habitat structure are drivers of the abundance and diversity of biological communities has been widely investigated. In this context, we assumed the hypothesis of heterogeneity habitat, in other words, habitat complexity leads to higher diversity of Odonata. Furthermore, we analyzed the influence of habitat structure on the distribution of this community, beyond to evaluate the effects of abiotic variables. Odonata larvae were collected with of sieves and by electrofishing in ten Neotropical streams belonging to the river basin Pirapó. Were recorded forty species of Odonata, distributed in eight families, Libellulidae highlighted in higher richness. The high gamma diversity and distribution of Odonata were associated with habitat heterogeneity present in these streams. However, the water abiotic variables also seem to have an effect on the distribution of species of Odonata, in view of the impact of the land use streams.